Integration of the Internet of things in Service Management: Designing a Monitoring Device for the Elderly (Global Journals of Research in Engineering, 2022)
Controlling and monitoring the elderly is an arduous and imperative task with regard to their physical safety. To assist in this aforementioned control, the main objective of this project is to present a real prototype for monitoring the elderly. Therefore, this prototype can become a support tool for managers of nursing homes, hospitals, etc., as it enables a more precise control of these elderly people. The case study method was applied in this research through a qualitative exploratory approach. It was concluded that the prototype presented has great potential to assist the administration of care services for the elderly, whose importance is even greater in the current context of a growing number of elderly people in the brazilian population. Finally, it is expected that the real prototype, when in the future it is transformed into a technological product on the market, will be a plausible way to carry out the control of the elderly in an agile way. An increase in the physical safety of the elderly is also expected, as this device can contribute to a reduction in incidents of falls.
Keywords: service management; elderly; internet of things; real prototype; monitoring device